From communities to corporations: The growth of mediation in Sri Lanka - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2001)
In this article I will outline the development of modern mediation in Sri Lanka. I use the term mediation to mean facilitative mediation. Accordingly, for the purposes of this article, mediation does not include processes such as conciliation or evaluative mediation, which are used in Sri Lanka, for example in industrial dispute resolution practice.